STRATEGI KOMUNIKASI PETUGAS KESEHATAN DALAM SOSIALISASI PENCEGAHAN COVID-19 DI DESA CIJUJUNG KECAMATAN CIBUNGBULANG - Nurmala , Rika; Ernawati , Erna; Muslikhah, Febri Palupi (JURNAL SAHID DA'WATII, 2023)
This study aims to determine the communication process carried out and how the communication strategy is carried out by health workers in socialization the prevention of Covid-19 in the village Cijujung cibungbulang sub-district. This study uses qualitative research methods using data collection techniques through interviews and documentation. The results of this study indicate that the communication process carried out by health workers in sicializing the prevention of covid-19 is by using verbal and nonverbal communication using group communication methods effectively and politely in socializing the preventing of covid-19 in the village of cijujung cibungbulang sub-district. The strategies carried out are (1) determining communicators for covid-19 health workers who have high attractiveness, credibility, power and have responsibility for the tasks that have been given. (2) setting targets, namely by gathering the cijujung village community. (3) dissemination of messages by health workers by socializing and also using electronic media such as WhattsappGroup. (4) the impact/effect that occurs is that people are more concerned about health protocols, sean from data collection and mobile patrols and the increasing enthusiasm of the community in participating in vaccinations.